Industrial Structure Upgrading and Marine Green Economy Efficiency - LIU Yan; HE Qiuju (Haiyang Kaifa yu guanli)
Industrial structure upgrading provides opportunities for the economy to achieve high-quality development under the new normal. Based on the panel data of 11 provinces (autonomous regions, municipalities) in China's coastal region from 2005 to 2015, this paper applies the Super-SBM model considering non-expected outputs to measure the marine green economy efficiency. A panel threshold regression model with industrial structure rationalization as the threshold variable is established to empirically analyze the impact of industrial structure advancement on the marine green economy efficiency. It is found that there is a non-linear relationship of increasing marginal effect between industrial structure advancement and marine green economy efficiency. The promotion effect of industrial structure advancement on marine green economy efficiency is significantly enhanced after crossing the threshold of the rationalization level of industrial structure. Therefore, in regions where industrial structure rationalization level is low, the emphasis of industrial structure adjustment should be on strengthening the integration and coordinated development of industries, facilitating the rational allocation and effective use of resources, laying a solid foundation for promoting the advanced industrial structure, and thus effectively improving the marine green economy efficiency.